EFEKTIVITAS SELF-VIDEO FEEDBACK DALAM MENINGKATKAN TEKNIK LOMPAT JAUH GAYA JONGKOK - Muh Fajar Sadiq Loji; Abu Bakar; Kevin Ferdo Watutama; Regina Kamisopa; Isak Samuel Yesawen (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Physical education learning in schools is generally still teacher-centered, limiting students’ opportunities to learn according to their developmental stages. This condition highlights the need for more varied instructional models, such as the use of visual media to encourage active student participation in the learning process. Instructional media serve as an effective tool for delivering information and learning materials, enabling students to better absorb content through sensory engagement. Media interact with students by stimulating their senses, sometimes requiring the integration of multiple senses to fully understand the conveyed message. This study aims to determine: (1) the improvement in the effectiveness of teaching the squat-style long jump using image-based media, and (2) the magnitude of this improvement. The subjects of this research were 18 fifth-grade students of SD 1 Sorong. The study employed descriptive and comparative quantitative statistical methods. The results indicate that: (1) there was an increase in the effectiveness of learning the squat-style long jump using image media, as evidenced by improved student learning mastery over four meetings, with an average increase of 6.1%; and (2) the use of image media contributed to an increase in students’ squat-style long jump performance by 12.50%. The t-test analysis showed that the calculated t-value (5.00) was greater than the t-table value (2.11), confirming a significant improvement in learning outcomes.